Tendencje do zmian przestrzennych dysproporcji rozwojowych w wybranych regionach Polski w latach 1999-2002 - Markowska-Przybyła, Urszula (Directions of changes of spatial development disparities in selected Polish regions between 1999-2002, 2006)
The processes of globalization and metropolizalion strengthen natural tendencies of space polarization. Inter- and intraregional development disparities are important challenge of the economic policy especially to regional and spatial policy. The aim of the paper is to analyze intraregional disparity using the example of selected Polish regions and particularly directions of changes of these disparities between 1999-2002.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 54-62